Pouvoir des séries télévisées - Jean-Pierre Esquenazi (Communication)
The author questions the notion of power as it relates to TV series. He rejects the concept of the all-powerful, deceiving cultural industry. The kind of power a TV series may exert lies in its ability to maintain its viewers in a state of fictional immersion, whereby they are suspended between two worlds, the world of fiction and the real world. The world of fiction is defined by its ability to continually expand its boundaries, over time, through the workings of its textual structuring. Examples of how TV series can increase the “density” of their worlds are selected from such productions as Law & Order, The Simpsons, NYPD Blue, Six Feet Under, and Battlestar Galactica.